2016
DOI: 10.3765/amp.v2i0.3757
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Neutralization in Japanese Monomoraic Lengthening

Abstract: Incomplete neutralization (IN) (Port et al. 1981, Fourakis & Iverson 1984, Port & O’Dell 1985) refers to cases in which two underlyingly distinct segments become nearly identical on the surface. IN has posed a challenge for traditional views of the phonetics-phonology interface. While classical modular feedforward architectures (e.g. Chomsky & Halle 1968, Bermúdez-Otero 2007) generally do not allow underlying phonological representations to directly affect phonetic realization, incompletely neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…For example, [baːlen] 'bags' has the same vowel durations as [daːlen] 'valleys', although their singular forms, [baːl] and [dal], differ in vowel length. In Japanese, however, Braver & Kawahara (2015) found that long vowels derived through a rule lengthening monomoraic Prosodic Words were 32 ms shorter than underlyingly long vowels, despite behaving as long in the phonology. Finally, a pilot study by Rudin (1980) found that Turkish long vowels derived from two short vowels, through a rule of intervocalic /g/-deletion, were 31 ms. longer than underlyingly long vowels (292 vs 261 ms).…”
Section: Complete and Incomplete Neutralizationmentioning
confidence: 91%
“…For example, [baːlen] 'bags' has the same vowel durations as [daːlen] 'valleys', although their singular forms, [baːl] and [dal], differ in vowel length. In Japanese, however, Braver & Kawahara (2015) found that long vowels derived through a rule lengthening monomoraic Prosodic Words were 32 ms shorter than underlyingly long vowels, despite behaving as long in the phonology. Finally, a pilot study by Rudin (1980) found that Turkish long vowels derived from two short vowels, through a rule of intervocalic /g/-deletion, were 31 ms. longer than underlyingly long vowels (292 vs 261 ms).…”
Section: Complete and Incomplete Neutralizationmentioning
confidence: 91%
“…In spite of the identical surface mora counts in (4b) and (4c) (due to lengthening in the case of (4b)), Braver & Kawahara (2016) found that the vowel durations of lengthened monomoraic nouns were not identical to those of underlyingly long nouns. In that study, twelve native speakers of Japanese were presented with 15 sets of three nouns: (a) a short noun with a case particle (no lengthening), (b) a short noun without a case particle (lengthening expected) and (c) an underlyingly long noun.…”
Section: Japanese Monomoraic Noun Lengtheningmentioning
confidence: 99%
“…In this section, I describe the phenomenon of incomplete neutralisation in Japanese monomoraic noun lengthening (Mori 2002, Braver & Kawahara 2014, 2016). This case will be used in §4 to illustrate the proposed model.…”
Section: Japanese Monomoraic Noun Lengtheningmentioning
confidence: 99%
See 2 more Smart Citations